An algebra problem by Mateus Gomes

Algebra Level 3

1 log 2 ( 2010 ! ) + 1 log 3 ( 2010 ! ) + + 1 log 2009 ( 2010 ! ) + 1 log 2010 ( 2010 ! ) = ? \dfrac{1}{\log_2(2010!)}+\dfrac{1}{\log_3(2010!)}+\cdots+\dfrac{1}{\log_{2009}(2010!)}+\dfrac{1}{\log_{2010}(2010!)} = \, ?

Notation : ! ! denotes the factorial notation. For example, 8 ! = 1 × 2 × 3 × × 8 8! = 1\times2\times3\times\cdots\times8 .


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Zee Ell
Aug 19, 2016

Due to the change of base theorem: \text {Due to the change of base theorem: }

1 l o g k ( 2010 ! ) = 1 l n ( 2010 ! ) l n ( k ) = l n ( k ) l n ( 2010 ! ) = l o g 2010 ! ( k ) \frac {1}{log_k(2010!)} = \frac {1}{\frac {ln(2010!)}{ln(k)}} = \frac {ln(k)}{ln(2010!)} = log_{2010!}(k)

Therefore, if we apply this for k = 2, 3, ... , 2009, 2010 \text {Therefore, if we apply this for k = 2, 3, ... , 2009, 2010}

(and (for the sake of aesthetics) we add 0 = l o g 2010 ! ( 1 ) ), we get: \text {(and (for the sake of aesthetics) we add } 0 = log_{2010!}(1) \text { ), we get: }

S = l o g 2010 ! ( 1 ) + l o g 2010 ! ( 2 ) + . . . + l o g 2010 ! ( 2009 ) + l o g 2010 ! ( 2010 ) = S = log_{2010!}(1) + log_{2010!}(2) + ... + log_{2010!}(2009) + log_{2010!}(2010) =

= l o g 2010 ! ( 1 × 2 × . . . × 2009 × 2010 ) = l o g 2010 ! ( 2010 ! ) = 1 = log_{2010!}(1 × 2 × ... × 2009 × 2010) = log_{2010!}(2010!) = \boxed {1}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...